KOMUNIKASI PEMASARAN UMKM DI MASA PANDEMI COVID 19 (Studi Kasus Cafe Kopierte) - Jafaruddin, Nurhana; Djayanti, Desi Dwi (Universitas Galuh, 2023)
The Covid-19 pandemic that occurred has caused many economic setbacks in the world, one of the fields that has been greatly affected, namely culinary. This is due to large-scale social restrictions set by the government. Culinary UMKM are one of the businesses that have been affected quite a lot because of this policy, because there is a tendency for consumers to only buy basic goods and ingredients. Cafe Kopierte is one of the UMKM affected by the co-19 pandemic. As a business that does not provide primary needs, it causes a decrease in demand for products from these UMKM. This is a new challenge for owners to maintain their business during the Covid 19 pandemic. This study aims to determine marketing communications carried out by Kopierte cafe owners to adapt during a pandemic. The research method used is descriptive qualitative. From the results of research conducted by the author, marketing communications carried out by cafe Kopierte are using two methods, namely personal selling and word of mouth. Personal selling is done by providing direct information via Whatsapp to customers. Word of Mouth which is done by providing the best information and service to customers who make purchases through online platforms